EVALUATION OF DIFFERENT DETECTION METHODS OF BIOFILM FORMATION IN CLINICAL ISOLATES OF STAPHYLOCOCCI - SAMANT SHARVARI A; PAI CHITRA G (International Journal of Pharma and Bio Sciences, 2012)
In this study 400 clinical isolates of staphylococci which include 250 isolates of S. aureus and 150 isolates of Coagulase negative staphylococci (CoNS) were screened for biofilm production. They were tested by three methods, Tissue culture plate (TCP) method, Tube method and Congo red agar (CRA) method. TCP method detected 105 (26.3%) isolates as strong biofilm producers, 68 (17%) as moderate biofilm producers and 227 (56.8%) as non producers of biofilm. Tube method and CRA method could detect 20.5% & 25.3% as strong producers and 63.8% and 74.8% as non producers respectively. TCP method could detect biofilm production in 45.6% of S.aureus and38.7% of CoNS. Maximum biofilm producing staphylococci was isolated from patients with artificial devices and the most common isolate was S.epidermidis. Biofilm production was more in Methicillin resistant strains and they showed higher degree of resistance to almost all the groups of antibiotics.